Ecological Corporative System Concept in Solving Problems of Ecological Estimation and Ecological Hygienic Normalization - Kozulia, T. V.; Sharonova, N. V.; Kozulia, M. M. (ХНУРЭ, 2010)
Approach of methodical application of concept of ecological corporative system (CES) in the system of ecological monitoring is shown in the article. Appropriateness of corporative approach application was indicated for problem solving of standardization of state parameters of environmental objects. The appropriate algorithms of the assessment of the health risk and of the ecological standardization problems were developed on basis of analysis of existent approaches of determination of system status and appropriateness of introduction of the risk-analysis for problem solving of state identification of CES.
Keywords: the ecological – hygienic assessment; the ecological standardization; the risk-analysis; the ecological corporative system